DFID’s partnerships with civil society organisations - A performance r eview - ICAI (Independent Commission for Aid Impact (ICAI), 2019)
DFID values civil society organisations (CSOs), but its funding and pa rtnership practices do not fully support the long-term health of the c ivil society sector.